Aid effectiveness in poverty alleviation in a post-conflict, post-disaster situation: A case study of district Swat, Pakistan - Ali, Murad (International Food Policy Research Institute, 2015)
This project aims at exploring the effectiveness of foreign aid within the 2005 Paris Declaration (PD) framework in a post-conflict and post-disaster zone. Focusing on the Swat region in the Khyber Pakhtunkhwa (KP) province in northern Pakistan, which witnessed unprecedented humanitarian crisis in the form of the 2009 militant insurgency and the 2010 floods, the key goal is to examine the effectiveness of donor-funded projects in rehabilitation and reconstruction. Using the 2005 PD doctrines, particularly the principles of ownership, alignment, and harmonisation, this research investigates to what extent aid donors and the Government of Pakistan (GoP) incorporated the PD commitments for making better use of foreign assistance. Thus, the project posits that efficient utilisation of foreign aid leads to effective financial and human resource management and better public service delivery and fits in well within the theme of ‘quality governance’ envisaged by the GoP in its Vision 2025.